Law No. 13 Of The Year 2013 On Amending The Trade Union Law No. 35 Of The Year 1976 By Means Of Extending The Term Of The Trade Union Session = قانون رقم 13 لسنة 2013 بتعديل قانون النقابات العمالية رقم 35 لسنة 1976 بمد أجل الدورة النقابية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.